2023
DOI: 10.1097/jcma.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ChatGPT on the pharmacist licensing examination in Taiwan

Abstract: Background: ChatGPT is an artificial intelligence model trained for conversations. ChatGPT has been widely applied in general medical education and cardiology, but its application in pharmacy has been lacking. This study examined the accuracy of ChatGPT on the Taiwanese Pharmacist Licensing Examination and investigated its potential role in pharmacy education. Methods: ChatGPT was used on the first Taiwanese Pharmacist Licensing Examination in 2023 in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…Similarly, ChatGPT failed the self-assessment tests respectively designed for urologists, 15 ophthalmologists, 16 gastroenterologists, 17 and parasitologists 18 and the Taiwanese Pharmacist Licensing Examination. 19 It should be highlighted that there is no any direct link between higher test scores from question banks like Kidney Self-Assessment Program and Nephrology Self-Assessment Program or even ABIM boards and being a better doctor for patient outcomes. The focus of our investigation was to assess the performance of AI technology in question answering and test-taking ability, rather than making any claims about its impact on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ChatGPT failed the self-assessment tests respectively designed for urologists, 15 ophthalmologists, 16 gastroenterologists, 17 and parasitologists 18 and the Taiwanese Pharmacist Licensing Examination. 19 It should be highlighted that there is no any direct link between higher test scores from question banks like Kidney Self-Assessment Program and Nephrology Self-Assessment Program or even ABIM boards and being a better doctor for patient outcomes. The focus of our investigation was to assess the performance of AI technology in question answering and test-taking ability, rather than making any claims about its impact on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This study used input items from the original Japanese text. Three studies compared ChatGPT’s (probably GPT-3.5 model based on the date of publication) performance on the same examination in English and another language, all showing a higher accuracy rate with English language inputs: on the Taiwan Pharmacist License Examination [ 5 ], in Chinese (54.5%) versus English (63.5%); the JMLE [ 12 ] in Japanese (52.8%) versus English (56.2%); and on the Israeli Hebrew OBGYN National Residency Examinations [ 14 ], in Hebrew (38.7%) versus English (60.7%). Furthermore, it has been confirmed that tuning the input prompts also improves the accuracy rate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from the use of AI techniques such as ChatGPT and GPT-4 to non-English language testing have been inconsistent. While ChatGPT stumbled on the Taiwanese Family Medicine Board Exam, with only 41.6% accuracy, and the Taiwanese Pharmacist Licensing Examination, scoring between 54.4% and 67.6%, GPT-4 showed potential by passing numerous years of the Japanese Medical Licensing Exams [23][24][25].…”
Section: Discussionmentioning
confidence: 99%